Architects – Founders of the Union of Architects in Irkutsk - Lyapin, Andrei (project baikal, 2015)
The article refers to foundation of the East-Siberian (Irkutsk) Branch of the Union of Architects. It presents the role of the Organizational Bureau in formation of the Union of Architects, which included such architects as K.V. Mital, B.M. Kerbel, I.G. Efimov, S.M. Zaslavsky, V.N. Kolyanovsky and V.N. Volkov. The article tells about the first Board of the Union of Architects in Irkutsk and gives the plan of the Union’s activity in the pre-war period.
Keywords: Union of Soviet Architects; East-Siberian Branch of the Union of Architects; architectural community; architecture of Irkutsk; chief architect of Irkutsk; architectural competitions